2014
DOI: 10.1111/mmi.12638
|View full text |Cite
|
Sign up to set email alerts
|

Replication fork inhibition in seqA mutants of Escherichia coli triggers replication fork breakage

Abstract: SeqA protein negatively regulates replication initiation in E. coli and is also proposed to organize maturation and segregation of the newly-replicated DNA. The seqA mutants suffer from chromosomal fragmentation; since this fragmentation is attributed to defective segregation or nucleoid compaction, two-ended breaks are expected. Instead, we show that, in SeqA’s absence, chromosomes mostly suffer one-ended DNA breaks, indicating disintegration of replication forks. We further show that replication forks are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 86 publications
(178 reference statements)
4
35
0
Order By: Relevance
“…We concluded that, while the rapidly growing wild-type cells have a single replication round per chromosome ( Figure 1E, the blue profile), cells with inhibited replication forks maintain up to three replication rounds in their chromosome (Figure 1, E and F). Since three replication rounds per chromosome is the highest replication complexity in growing cells reported in the literature (Lane and Denhardt 1975;Martín and Guzmán 2011;Rotman et al 2014), both our and the literature data suggest "CRC8" in E. coli as a natural limit showing static features. …”
mentioning
confidence: 81%
See 4 more Smart Citations
“…We concluded that, while the rapidly growing wild-type cells have a single replication round per chromosome ( Figure 1E, the blue profile), cells with inhibited replication forks maintain up to three replication rounds in their chromosome (Figure 1, E and F). Since three replication rounds per chromosome is the highest replication complexity in growing cells reported in the literature (Lane and Denhardt 1975;Martín and Guzmán 2011;Rotman et al 2014), both our and the literature data suggest "CRC8" in E. coli as a natural limit showing static features. …”
mentioning
confidence: 81%
“…Indeed, both the HU treatment, on the one hand, and the seqA and rep defects, on the other hand, induce formation of double-strand DNA breaks (Michel et al 1997;Mohana-Borges et al 2000;Rotman et al 2014), perhaps the most serious of all chromosome lesions (Resnick 1978;Iliakis 1991). At the same time, both the natural CRC8 and the functional CRC22 limits are well-tolerated, suggesting robust chromosomal repair mechanisms.…”
Section: A System To Maximize Crcmentioning
confidence: 93%
See 3 more Smart Citations